Erratum: On the nonlinear dynamics of electro-magnon excitations in the BaTiO3/Fe nanostructured multiferroic composite material. (21st September 2018) - Paglan, P. A.; Nguenang, J. P.; Ruffo, S.
Abstract: Original article: EPL, 122 (2018) 68001 .